The Efficacy and Safety of Cystic Fibrosis Gene Therapy Clinical Trials: A Systematic Review and Meta-Analysis - Al-Taani, Ghaith; Yehya, Alaa (Jordan Medical Journal, 2022)
Background Gene therapy has been proposed as a treatment approach for cystic fibrosis by replacing the single defective gene, cystic fibrosis transmembrane regulator (CFTR), through topical lung delivery. Relatively few studies have addressed gene therapy for cystic fibrosis. Objectives Via referral to the published literature, this study aimed to identify any success of the gene therapy approach for cystic fibrosis regarding experimental and routine clinical outcomes in different drug development stages, and to determine any adverse effects noted. Methodology A search of the PubMed database (NCBI) for 1989–2020 was made using predefined selection criteria for clinical trials on patients with cystic fibrosis receiving viral and non-viral lung delivery systems of the CFTR gene. Several features in the reviewed studies were examined, including clinical phase (1–3), sample size, delivery target cells/vector, and reported adverse effects. A quantitative estimate of treatment intervention success was evaluated using a meta-analysis approach. Results A total of 20 studies with 549 patients were included in the review. The studies involved the delivery of the defective gene to the lung, nasal mucosa, and sinuses, and were mainly phase 1–2, randomized controlled trials; there were no phase three studies. The vector for gene transfer was liposome or viral. % predicted FEV1 was statistically significant between intervention and control patients in two trials. Gene transfer was detected to a higher degree in intervention patients than control; this outcome measure was assessed using bronchoscopy assessment of vector-specific DNA and mRNA expression in lung and nasal mucosa. These effects, however, were temporary. The safety of the gene therapy approach was confirmed. Conclusion Reportedly, the gene therapy approach is safe but has limited and temporary efficacy. Newer approaches should thus be engineered to deliver the necessary genetic material with the desired, full-scale efficacy.